Problems and Needs for Development of Retail Operators Thong Fah Pracharath, Yala province. - E-sor et al., Apsorn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The propose of this research is to study the problems in operation and the needs for development of Thong Fah Pracharath retailers in Yala province. The research was conducted quantitatively by using a questionnaire to gather data from 195 retailers, as a sample group, which applied a technique of accidental sampling. The statistics used to analyze data were frequency, percentage, mean, and standard deviation. The results indicated that problems in operation were at moderate level, which including problems in finance and accounting (x ̅ = 2.16, SD. = 0.65), problems in administration (x ̅ = 1.96, SD. = 0.63), and problems in marketing (x ̅ = 1.87, SD. = 0.60). In addition, it was also found that the needs for development in terms of capital need was at high level as a whole (x ̅ = 2.34, SD. = 0.63) meanwhile, both knowledge need and product/equipment development need were at moderate level as a whole (x ̅ = 2.33, SD. = 0.67, x ̅ = 2.25, SD. = 0.62 respectively). Article history : Received 11 June 2019 Revised 2 September 2019 Accepted 9 September 2019 SIMILARITY INDEX = 1.63 %